Proximate, Mineral, Amino Acid Composition, and Bioactive Properties of Dough Meals Supplemented with African Walnut Flour - Mayomi, Peace Tumininu; Aderinola, Taiwo Ayodele (Food Science and Engineering, 2024)
This study investigated the impact of African walnut flour supplementation on the nutritional and bioactive properties of dough meals formulated with varying proportions of plantain flour. The proximate composition, mineral content, amino acid profile, color characteristics, antioxidant and anti-diabetic properties were analyzed for five different formulations: 100% plantain flour (P100), 95% plantain flour with 5% African walnut flour (PAW95), 90% plantain flour with 10% African walnut flour (PAW90), 85% plantain flour with 15% African walnut flour (PAW85), and 80% plantain flour with 20% African walnut flour (PAW80). The proximate analysis revealed significant variations, with moisture content ranging from 53.71% to 71.89%, ash content from 0.77% to 1.28%, and protein content from 3.38% to 11.14%. Notably, PAW80 showed the highest protein content. Mineral analysis showed that calcium, potassium, and magnesium levels varied significantly across the samples, with the highest calcium content observed in PAW80 (32.55 mg/kg) and the highest potassium content in PAW95 (47.80 mg/kg). Amino acid analysis indicated that essential amino acids, particularly leucine, valine, and lysine, were present in higher concentrations in the supplemented samples compared to P100. Antioxidant assays indicated that PAW80 had the highest 2,2-diphenyl-1-picrylhydrazyl (DPPH) (67.22%) and hydroxyl (73.66%) free radical scavenging activities. The in vitro anti-diabetic assays revealed that α-amylase and α-glucosidase inhibitory activities were enhanced with higher walnut flour supplementation. These findings suggest that African walnut flour can significantly enhance the nutritional quality and bioactive properties of plantain-based dough meals, and thus make it a functional food with potential health benefits.